Peculiarities of early diagnosis and tactics of treatment in an acute pancreatitis in pregnant women - Ya. P. Feleshtynskyi; О. V. Golyanovskyi; Т. P. Pavliv (Клінічна хірургія)
Objective. Improvement of the treatment results of an acute pancreatitis in pregnant women, using enhanced early diagnosis and tactics of treatment.